1997
DOI: 10.1111/j.1751-1097.1997.tb01883.x
|View full text |Cite
|
Sign up to set email alerts
|

Photooxidation of Tryptophan: O2(1Δg) versus Electron‐Transfer Pathway

Abstract: Tris (2,2'-bipyridyl)ruthenium(II)chloride hexahydrate (Ru[bpy]3(2+)) free in solution and adsorbed onto antimony-doped SnO2 colloidal particles was used as a photosensitizer for a comparison of the O2(1 delta g) and electron-transfer-mediated photooxidation of tryptophan (TRP), respectively. Quenching of excited Ru(bpy)3(2+) by O2(3 sigma g-) in an aerated aqueous solution leads only to the formation of O2(1 delta g) (phi delta = 0.18) and this compound was used as a type II photosensitizer. Excitation of Ru(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 45 publications
2
44
0
Order By: Relevance
“…Thus, these results are not in agreement with those obtained for the DMA photooxidation, indicating that other photoreaction process, probably an electron transfer process, is also involved in the decomposition of Trp sensitized by Pd(II) porphyrin 3 . In addition, the photosensitized oxidation of Trp was found to be more than two orders of magnitude more efficient via electron transfer than via O 2 ( 1 Δ g ) (49).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, these results are not in agreement with those obtained for the DMA photooxidation, indicating that other photoreaction process, probably an electron transfer process, is also involved in the decomposition of Trp sensitized by Pd(II) porphyrin 3 . In addition, the photosensitized oxidation of Trp was found to be more than two orders of magnitude more efficient via electron transfer than via O 2 ( 1 Δ g ) (49).…”
Section: Resultsmentioning
confidence: 99%
“…The ascending branch decrease of the dimer absorbance peak observed in the presence of Trp beforeand after 10 min irradiation time could be associated to a decrease in dye dimerisation. Trp, which was non-specific singlet oxygen quencher(Wessels et al 1997), did not protect the S. aureus bacteria, after 10 min of MB photosensitization. Probably the difference between the dye spectra profile in the presence of S. aureus bacteria without or with Trp may be attributed to our bacterial system and Trp molecules.…”
mentioning
confidence: 99%
“…From these plots, the values of the k Trp obs were calculated for P and dyads (Table 1). As observed in Table 1, higher photo‐oxidation rates were obtained using dyads as sensitizers than with P. In previous studies, the photosensitized oxidation of Trp was found to be more than two orders of magnitude more efficient via electron transfer than via O 2 ( 1 Δ g ) (32). Comparing the kinetic results of Trp and DMA in DMF, it can be observed that the ratio K Trp obs /k DMA obs takes values of 0.44, 7.7 and 25.3 for P, P‐C 60 and ZnP‐C 60 , respectively.…”
mentioning
confidence: 75%